ABRIDGING SENTENCES OF PRÉCIS WRITING IN AESOP FABLES - Shandy, Muhammad Luthfi; Natsir, Muhammad (TRANSFORM: Journal of English Language Teaching and Learning, 2013)
ABSTRACTThis study is concerned with writing, focusing on the abridging sentences ofprécis writing used in Aesop Fables. This study was conducted by using descriptivequalitative design. There are ten fables of Aesop in this study taken from The Book ofAesop (Townsend: 1869). There were 103 forms. The result of data analysis showed thetotal number in types of abridging were: by reducing a clause to a phrase 55.34 %, byreducing a phrase to a word 10.68 %, change the direct speech to indirect speech 16.5%, and by reducing a clause to a word 17.48 %. It means that by reducing a clause to aphrase is the dominant types of abridging sentences used in Aesop fables. It is 52.7 %.The reason why abridging sentences by reducing a clause to a phrase is dominantbecause in all ten of the fables use many long clauses that can be reducing to phrases.There are many clauses which can be reducing to a simpler term of phrases. And theresult based on the context of the form were: human 9.2 %, animal 73.55 %, thing 5.75%, and situation 11.5 %. It means that the context of animal is the most dominantcontext. Then it is found that the ten fables are dominantly use the type of abridging byreducing a clause to a phrase in the context of animal.Keywords: Writing, Précis writing, Abridging Sentences*Graduate